2012
DOI: 10.1115/1.4007166
|View full text |Cite
|
Sign up to set email alerts
|

On The Nonlinear Dynamics of Two Types of Backup Bearings — Theoretical and Experimental Aspects

Abstract: The possible contact between rotor and stator canfor some cases be considered a serious malfunction that may lead to catastrophic failure. Rotor rub is considered a secondary phenomenon caused by a primary source that leads to a disi'uption of the normal operational condition. It arises from sudden mass unbalance, instabilities generated by aerodynamic and hydrodynamic forces in seals and bearings among others. The contact event gives rise to normal and friction forces exerted on the rotor at impact events. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…By a point-point contact model, Ma et al [2] investigated fault characteristics of a single span rotor system with two disks when the rubbing between a disk and an elastic rod occurs. In order to reduce the rub related severity in friction, Lahriri et al [3,4] developed a new unconventional backup bearing, which utilizes four pin connections to force the rotor to the center and mitigate the lateral motion. In this way, the full annular rubbing can be changed into four-point rubbing.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By a point-point contact model, Ma et al [2] investigated fault characteristics of a single span rotor system with two disks when the rubbing between a disk and an elastic rod occurs. In order to reduce the rub related severity in friction, Lahriri et al [3,4] developed a new unconventional backup bearing, which utilizes four pin connections to force the rotor to the center and mitigate the lateral motion. In this way, the full annular rubbing can be changed into four-point rubbing.…”
Section: Introductionmentioning
confidence: 99%
“…Under this condition, the rubbing force can change the motion direction of the rotor. Aiming at the point rubbing, lots of studies [1][2][3][4][5][6] have been carried out. Han et al [1] analyzed periodic motions of a rotor system with two disks where the rub-impacts occur at fixed limiter for a test rig with dual disks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3. The rotor consists of an inner steel shaft 24 with the axial permanent magnet bearing (PMB) 28 bolted onto one end and a compressor wheel 19 bolted onto the 1 Tilting frame, 2 Gimbal, 3 Housing, 4 Accelerometer, 5 Power Supplies for AMBs, 6 Pneumatic Supplies, 7 Pneumatic Actuator Position Sensor, 8 Pneumatic Actuator for Pitching, 9 Pneumatic Actuator for Surging, 10 Rail, 11 Translating Frame, 12 Proximity Probe Conditioners, 13 Electronic Cabinet. other end.…”
Section: Housing and Rotormentioning
confidence: 99%
“…A similar idea was given by Simon [16], who simulated and tested the disc collisions in different safety bearing geometries. The first attempt to introduce the idea of conscripted movement with pins was experimentally tested by Lahriri et al [11], in collaboration with PUC-Rio in 2011, which used an experimental test bench from the works of Alvarado [1] and Segayer [15]. Furthermore, an effective control that avoids a rotor to rub was proposed by Ginzinger [8] using active bearings and further developed by Jiang et al [10], whose works have shown that impacts were prevented and stabilization was achieved.…”
Section: Introductionmentioning
confidence: 99%